2012
DOI: 10.1039/c2ee02480b
|View full text |Cite
|
Sign up to set email alerts
|

Replacing fossil based PET with biobased PEF; process analysis, energy and GHG balance

Abstract: An energy and greenhouse gas (GHG) balance study was performed on the production of the bioplastic polyethylene furandicarboxylate (PEF) starting from corn based fructose. The goal of the study was to analyze and to translate experimental data on the catalytic dehydration of fructose to a simulation model, using the ASPEN Plus modeling software. The mass and energy balances of the simulation model results were then used as inputs for a process chain analysis (by application of the life cycle assessment methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
399
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(430 citation statements)
references
References 31 publications
4
399
1
2
Order By: Relevance
“…Some of these catalytic conversions show good promise, and the company Avantium has announced the start of a pilot plant for the production of FDCA and its methyl esters from fructose, via ethers of HMF, using a Co/Mn/Br catalyst (Munoz de Diego et al 2011;van Putten et al 2013). An energy and greenhouse gas balance study based on this chemical process, assuming a conversion efficiency from fructose to FDCA of 38-47 %, concluded that PEF production has the potential to reduce the nonrenewable energy use by approximately 40-50 %, while greenhouse gas emissions can be reduced by 45-55 % compared to the established PET process (Eerhart et al 2012).…”
Section: Chemical Production Of 5-(hydroxymethyl)furfural and 25-furmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these catalytic conversions show good promise, and the company Avantium has announced the start of a pilot plant for the production of FDCA and its methyl esters from fructose, via ethers of HMF, using a Co/Mn/Br catalyst (Munoz de Diego et al 2011;van Putten et al 2013). An energy and greenhouse gas balance study based on this chemical process, assuming a conversion efficiency from fructose to FDCA of 38-47 %, concluded that PEF production has the potential to reduce the nonrenewable energy use by approximately 40-50 %, while greenhouse gas emissions can be reduced by 45-55 % compared to the established PET process (Eerhart et al 2012).…”
Section: Chemical Production Of 5-(hydroxymethyl)furfural and 25-furmentioning
confidence: 99%
“…Given the large market volume of these currently oil-based plastics [approximately 50 million tonnes per year for PET alone (de Jong et al 2012)], the possible impact of FDCA can be very high. Especially for PET-based bottles and packaging materials [approximately 15 million tonnes per year (Eerhart et al 2012)], there is a strong "green" customer demand, as illustrated by press releases by the Coca-Cola company and Danone. These companies have publicly stated the intent to develop and use FDCA-based PEF bottles, e.g., in collaboration with the company Avantium, which is developing a chemical FDCA production and polymerization process (Coca-Cola 2011;Avantium 2012).…”
Section: Potential Of Bio-based 25-furandicarboxylic Acidmentioning
confidence: 99%
“…Soluble metal bromide catalysts (Co/Mn/ Br) in acetic acid, normally employed for the conventional oxidation of para-xylene to terephthalic acid, have been tailored for the HMF oxidation. [12,13] Also, recoverable supported metallic nanoparticles, mainly Pt-, [14][15][16][17] Ru-, [18,19] and Au-based, [20][21][22][23][24] and bimetallic catalysts [25][26][27] that permit the reaction in an aqueous medium by using molecular oxygen or air have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Their work leads to the ready synthesis of polyethylene furandicarboxylate-also designated polyethylene furanoate, PEF-which is a viable substitute for polyethylene terephthalate (PET) [17], and is used extensively as a container material for portable water and mineral drinks.…”
Section: Converting Carbon Dioxide To Fuel and Other Productsmentioning
confidence: 99%